O trudnej sztuce obywania się bez granic - Lisiecki, Stanisław (Człowiek i Społeczeństwo, 2014)
The author focuses on demonstrating that, contrary to the currently popular thesis of the disappearance of the “old” borders, in many cases we can talk about the emergence of “new” borders and the renaissance of ethnic boundaries (Scotland, Catalonia, Silesia). The text discusses the phenomenon of ethnic segmentation in multi-ethnic and multicultural cities. It gives an example of German cities (Berlin, Frankfurt am Main and cities in North Rhine-Westphalia). The author shows that talking about the end of the borders appears to be too early and that it is still worth dealing scientifically with the socially constructed borders.